2020
DOI: 10.3390/s20247340
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Characteristics of a Large-Area n-MoS2/p-Si Heterojunction Structure Formed through Sulfurization Process

Abstract: Two-dimensional (2D) materials, such as molybdenum disulfide (MoS2) of the transition metal dichalcogenides family, are widely investigated because of their outstanding electrical and optical properties. However, not much of the 2D materials research completed to date has covered large-area structures comprised of high-quality heterojunction diodes. We fabricated a large-area n-MoS2/p-Si heterojunction structure by sulfurization of MoOx film, which is thermally evaporated on p-type silicon substrate. The n-MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Zhang et al reported that high-quality and large-scale MoS2 films can be obtained by providing controllable deposition of films using the sputtering technique, also MoS2/Si-based devices with high performance can be developed [23]. As far as it can be seen from the literature, there are few studies on the electrical characteristics of MoS2/p-Si heterostructured diodes in which different metal electrodes are developed by vacuum techniques [24,25]. Besides, developing heterostructured devices, it can be considered that these studies aim to reach high-performance devices through the integration of twodimensional materials such as MoS2 with Si-based electronics [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported that high-quality and large-scale MoS2 films can be obtained by providing controllable deposition of films using the sputtering technique, also MoS2/Si-based devices with high performance can be developed [23]. As far as it can be seen from the literature, there are few studies on the electrical characteristics of MoS2/p-Si heterostructured diodes in which different metal electrodes are developed by vacuum techniques [24,25]. Besides, developing heterostructured devices, it can be considered that these studies aim to reach high-performance devices through the integration of twodimensional materials such as MoS2 with Si-based electronics [26].…”
Section: Introductionmentioning
confidence: 99%
“…electrical characteristics of MoS2(15 heterostructured diodes in which different metal electrodes are developed by vacuum techniques. Kim et al reached a rectification ratio of 10 4and an ideality factor of 1.53 with a MoS2 (15 nm)/p-Si diode with an ohmic Ti/Au electrode created by vacuum evaporation[25]. Y. Zhang et al reported that the rectifying ratio of the device with MoS2 layer thickness of 10 nm formed by sputtered Ag electrodes was obtained to be 1.05×10 2 with an ideality factor of 1.05.…”
mentioning
confidence: 99%